SURABAYA-SMART SUSTAINABLE TOURISM: KONSEP SMART TOURISM TERINTEGRASI DENGAN STRATEGI DEEP PENTAHELIX SEBAGAI LANDASAN PENGEMBANGAN POTENSI PARIWISATA DI SURABAYA - Anik Kurnia Ningsih; Jaka Nugraha (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The Covid-19 pandemic has had a negative impact on all aspects of the economy, especially tourism. One of the affected areas is Surabaya. Surabaya has tourism potential which is very potential to be developed and become the government's attention. With Surabaya's tourism potential being quite large, the contribution of the tourism sector to Regional Revenue has not been maximized. Based on these problems, a solution is needed to overcome economic problems in the Surabaya tourism sector. The purpose of writing this paper is to describe the Surabaya-Smart Sustainable Tourism concept, development targets, SWOT analysis, the role of the deep pentahelix, SWOT analysis, and financial projections. The research method used is a literature study with a descriptive writing method and a qualitative approach. From this writing it is known that Surabaya-Smart Sustainable Tourism is a smart Surabaya tourism development concept that involves all elements of the deep pentahelix. Development targets using SMART analysis and contribution to SDGs, industrial revolution 4.0, and society 5.0, deep pentahelix has a very important role for concepts, SWOT analysis and financial projections show results that are feasible to implement.